Social inequality and possible impacts on High School offering in Belém PA - Keline do Socorro Rodrigues de Souza; João Paulo da Conceição Alves (Revista Diálogo Educacional)
In this study, we aim at discussing about possible causes of a weakening in High School offering in Pará State, highlighting the Social Vulnerability Index (IVS) results related to the city of Belém-PA, especially their education consequences. The research was carried out by the adoption of a qualitative approach, materialized through document analysis. We could observe that, even though education is one of the dimensions assessed by the IVS, education public policy in force do not seek to overcome any of the causes of problems that might affect this education stage. Such examples would be the Brazilian Common Core Curriculum for High School, and the New High School, at a federal level, as well as the programs “Bora Estudar” (Let’s study), and “Escola que transforma” (School that transforms) by the State Secretary for Education in Pará (SEDUC-PA). In other words, it is not enough to offer precarious education and to create public policies which do not align with goals that have guided education as a fundamental right and of social quality. Based on that, we could realize that, as public policies keep on being dictated by multilateral organisms’ guidelines, both the IVS and the Basic Education Development Index (IDEB) results may be used to ground counter-reforms for economical, social and political adjustment, as status quo maintenance is a capitalist project in a perpetual movement of self-renovation.